APPLICATION OF TECHNOLOGY PRICK THERMAL PROCESS AND INTEGRATION IN ETHANOL PRODUCTION IPOMOEA BATATAS (SWEET POTATO) - Erazo E., Raymundo (2006)
This paper aims to develop the thermal process integration and PINCH applying technology to the production of ethanol from sweet potato variety INIA 306 Huambachero. The first part is presented, process technology, which consisted of a first tase hydrolysis of starch. a brewing malt enzymes obtained in a maximum time of 20 minutes, followed by fermentation with yeast saccharomyces cerevisiae. providing a yield of 85 to 95 liters of ethanol per ton of sweet potato and representing about economic benefit of up to 25% reduction in production costs of ethanol per liter compared with conventional alcohol as raw sugar cane molasses.